Review of Non-Literary and Literary Text in Translation (based on an analysis of an EU institutional-legal text and novel excerpt “The Shack” by William P. Young) by Klaudia Bednárová-Gibová (American & British Studies Annual, 2013)
Review of Non-Literary and Literary Text in Translation (based on an analysis of an EU institutional-legal text and novel excerpt “The Shack” by William P. Young) by Klaudia Bednárová-Gibová (Prešov: Acta Facultatis Philosophicae Universitatis Prešoviensis, 2012, ISBN 978-80-555-0612-8)